On Curiosity - Frank Cochoy (Mattering Press, 2016)
What draws us towards a shop window display? What drives us to grab a special offer, to enter the privileged circle of premium newspaper subscribers, to peruse the pages of an enticing magazine? Without doubt, it is curiosity - that essential force of everyday action which invites us to break from our habits and to become transported beyond our very selves. Curiosity (whether healthy or unhealthy) is one of the favourite tricks of market seduction. Capturing a public - attracting the attention of a reader, seducing a customer, meeting the expectations of a user, persuading a voter ... - often requires the construction of a set of technical devices that can play upon people's inner motivations. Cochoy invites us to take a sociological trip into these cabinets of curiosity, accompanied throughout by Bluebeard, a fairy tale that is both a model of the genre and a pure curiosity machine. At once a work of history and economic anthropology, the book meticulously analyses the devices designed by markets to arouse, excite, and sustain curiosity: a window display, practices of 'teasing', packaging, bus shelters, mobile internet technologies, to name but a few. In the Bettencourt and Strauss-Kahn affairs and the Wikileaks controversy, Cochoy also uncovers the work of investigative journalism and its attention-grabbing 'scoops', revealing the secrets of the revealers of secrets. Available in English for the first time, this major work will arouse readers' curiosity over the course of its unusual and colourful journey. By the end, now better informed and more cautious, they will be able to identify the traps of which they are the target. So long as curiosity is kept at bay, at least!